Living on the Line: Gendered Invisibilities among Queer Women and Transmen in Indonesia. Issue 2 (3rd April 2023) - Jansen, Wikke
ABSTRACT: This article explores the lived experiences of queer Indonesian women and transmen in urban centres in Bali and Java. It is based on a multi-sited ethnographic study that took place between 2017 and 2020 among queer individuals and groups, including activists, scholars and religious leaders. The recent surge in attention to the variety of subjectivities gathered under the catch-all terms 'LGBT (Lesbian, Gay, Bisexual and Transgender)' and 'queer' has been accompanied by an increase in institutionalised discrimination and social stigmatisation. Although these developments affect all queer Indonesians, the experiences of those who were labelled female at birth are coloured by their particular positions on a familial, societal, legal and religious level. This article analyses the diverse range of experiences, strategies and alignments that arise from the relative invisibility and exclusion of queer women and transmen from queer as well as heteronormative spaces and discourse. I suggest that while invisibility contributes to the marginalisation of queer women and transmen in Indonesia, it is also instrumental to how they negotiate their position in a heteronormative context. Therefore, the increased visibility of the queer community risks intensifying multiple marginalisations along the axes of gender, class and religion.